Testing the Mediating Role of Dividend Policy in the Relationship between Profitability and Firm Value in the Mining Sector Listed on the Indonesia Stock Exchange (2020–2023) - Apolinaris S. Awotkay; Yumiad Fernando Richard; Ni Luh Putu Nita Yulianti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines the effect of profitability on firm value, both directly and through dividend policy as an intervening variable, in mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. The study employs a quantitative approach using secondary data. Data analysis is conducted using multiple linear regression and mediation testing through path analysis, processed with SPSS version 25. The sample is selected using purposive sampling; from a population of 80 firms, 13 companies meet the criteria and are included in the analysis. Profitability (ROE) serves as the independent variable, firm value (Tobin’s Q) as the dependent variable, and dividend policy (DPR) as the intervening variable. The results indicate that profitability has a positive and significant effect on firm value, profitability has a positive but insignificant effect on dividend policy, dividend policy has a negative and insignificant effect on firm value, and dividend policy does not mediate the relationship between profitability and firm value. These findings suggest that improvements in profitability contribute to firm value primarily through a direct pathway rather than through dividend policy as an intervening mechanism.